Partisan veto players in Australia, Denmark, Finland and Germany: Government status and legislative behavior - Steffen Ganghof; Thomas Bräuninger (Max Planck Institute for the Study of Societies, 2003)
In parliamentary systems, parties compete for votes and offices in the electoral arena but in many systems they also cooperate in the legislative arena. This paper examines the question of whether the government status of parties affects their legislative behaviour and, hence, policy outcomes. We develop a simple veto player model that includes parties' positional goals (vote, office, etc.) to formalize the notion of accommodating legislative behaviour. The model predicts that government parties are most accommodating while opposition parties are least accommodating. The hypothesis is then tested by comparing two pairs of most similar political systems: Danish and Finnish coalition governments, as well as German and Australian bicameralism. The case studies support the main hypothesis that government status systematically affects parties' level of accommodation. We conclude that this has important implications for the two major approaches in comparative institutional analysis advanced by Lijphart (1999) and Tsebelis (2002). Whilst Lijphart's distinction between joint and divided responsibility cannot provide a consistent theoretical rationale of his twodimensional map of democracies, Tsebelis' conception of purely policy-seeking actors may be insufficient to adequately identify veto players in comparative research. – – In parlamentarischen Systemen konkurrieren Parteien um Wählerstimmen und Ämter, aber in vielen Systemen kooperieren sie auch in der legislativen Arena. Das Papier untersucht die Frage, ob der Regierungs- versus Oppositionsstatus von Parteien ihr legislatives Verhalten und somit Politikergebnisse beeinflusst. Wir entwickeln ein einfaches Vetospielermodell, das positionale, das heißt auf Wählerstimmen oder Ämter bezogene, Erwägungen in den Politikpräferenzen von Parteien berücksichtigt und damit die verbreitete Vorstellung von (nicht-)akkommodierendem legislativem Verhalten formalisiert. Das Modell impliziert, dass Regierungsparteien am stärksten akkommodierend sind, Oppositionsparteien am wenigsten. Die Hypothese wird mit Hilfe zweier Vergleiche in einem most similar case Design getestet. Der erste Vergleich stellt dänische und finnische Koalitionsregierungen einander gegenüber, der zweite das deutsche und das australische Zweikammersystem. Die Fallvergleiche stützen die Hypothese, dass der Regierungsstatus von Parteien beeinflusst, wie akkommodierend sie sich verhalten. Das Ergebnis hat wichtige Implikationen für zwei bedeutende Ansätze in der vergleichenden Analyse politischer Institutionen: Lijpharts' Unterscheidung von Mehrheitsund Konsensdemokratien und Tsebelis' Vetospielertheorie. Lijpharts theoretische Gegenüberstellung von 'gemeinsamer' und 'getrennter' Verantwortung für Politikergebnisse liefert keine konsistente theoretische Begründung für seine zweidimensionale Messung moderner Demokratien; Tsebelis' Konzeption von Akteuren, die nur an Verbesserungen im Policy-Raum interessiert sind, scheint nicht hinreichend, um in vergleichenden Studien Vetospieler angemessen zu identifizieren.
Keywords: 300